2019
DOI: 10.1016/j.dam.2019.04.017
|View full text |Cite
|
Sign up to set email alerts
|

A note on antimagic orientations of even regular graphs

Abstract: Motivated by the conjecture of Hartsfield and Ringel on antimagic labelings of undirected graphs, Hefetz, Mütze, and Schwartz initiated the study of antimagic labelings of digraphs in 2010. Very recently, it has been conjectured in [Antimagic orientation of even regular graphs, J. Graph Theory, 90 (2019), 46-53.] that every graph admits an antimagtic orientation, which is a strengthening of an earlier conjecture of Hefetz, Mütze and Schwartz. In this paper, we prove that every 2d-regular graph (not necessarily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…Particularly, they showed that every orientation of stars (other than K1,2), wheels, and complete graphs (other than K3) is antimagic. Conjecture 1 has been also verified for regular graphs [9,13,15,17], biregular bipartite graphs with minimum degree at least two [14], Halin graphs [20], graphs with large maximum degree [18], and graphs with large independence number [16]. In this paper, by supporting Conjecture 1 we obtain the results below.…”
Section: Introductionsupporting
confidence: 74%
“…Particularly, they showed that every orientation of stars (other than K1,2), wheels, and complete graphs (other than K3) is antimagic. Conjecture 1 has been also verified for regular graphs [9,13,15,17], biregular bipartite graphs with minimum degree at least two [14], Halin graphs [20], graphs with large maximum degree [18], and graphs with large independence number [16]. In this paper, by supporting Conjecture 1 we obtain the results below.…”
Section: Introductionsupporting
confidence: 74%
“…Conjecture 1.1 has been verified to be true for odd regular graphs [9], disjoint union of cycles or connected 2d-regular graphs with d ≥ 2 by Li, Song, Wang, Yang, and Zhang [11], and disconnected 2d-regular graphs with d ≥ 2 by Yang [13]. A bipartite graph G with bipartition (A, B) is (a, b)biregular if each vertex in A has degree a and each vertex in B has degree b. Shan and Yu [12] recently proved that every (a, b)-biregular bipartite graph admits an antimagic orientation.…”
Section: Conjecture 11 ([9]mentioning
confidence: 99%
“…As a relaxation of this problem, Hefetz, Mütze, and Schwartz [9] proposed the following conjecture. Very recently, Conjecture 1.1 has been verified to be true for regular graphs (see [9,10,12]), and biregular bipartite graphs with minimum degree at least two by Shan and Yu [11]. Motivated by the work of Yilma [13], we establish more evidence for Conjecture 1.1 in this paper by studying antimagic orientations of graphs with large maximum degrees.…”
Section: Introductionmentioning
confidence: 62%
“…The main idea of the proofs of Theorem 1.2 and the preliminary results (stated and proved in Section 2) is to use Eulerian orientations. This strategy was first used in [9] and then in [10,12]. Our method here is more involved to obtain antimagic orientations of such graphs.…”
Section: Introductionmentioning
confidence: 99%